ANALISIS PROBLEMATIKA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA SEKOLAH KATEGORI TERPENCIL DI SD - Saifullah, Muhammad Ghulam; Istikomah, Istikomah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Islamic Religious Education (PAI) plays a strategic role in shaping the character of students to be faithful, pious, and noble. However, its implementation in elementary schools, especially in areas with limited resources, still faces various obstacles. This study aims to analyze the problems of Islamic Religious Education (IRE) learning at SDN 2 Gebang Sidoarjo, which is classified as a school in the 3T (remote, outermost, disadvantaged) category. The research focuses on identifying problems in PAI learning in terms of teacher human resources, learning facilities and infrastructure, learning methods, and student interest and participation. This study uses a descriptive qualitative approach with a case study method. Data collection was carried out through participant observation, in-depth interviews with the principal, IRE teachers, and students, as well as analysis of learning documents. Data analysis was carried out using the Miles and Huberman interactive model, which includes the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that PAI learning at SDN 2 Gebang Sidoarjo faces various interrelated problems, including the limited number and competence of PAI teachers who must also serve as classroom teachers, the lack of learning support facilities and infrastructure, the dominance of conventional learning methods due to the multi-grade system, and low student interest and participation influenced by a lack of learning variety and family support. The conclusion of this study emphasizes that improving the quality of PAI learning requires comprehensive improvement efforts through strengthening teacher competence, providing adequate facilities and infrastructure, applying contextual and innovative learning methods, and strengthening collaboration between schools, parents, and the community. ABSTRAK Pendidikan Agama Islam (PAI) memiliki peran strategis dalam membentuk karakter peserta didik yang beriman, bertakwa, dan berakhlak mulia. Namun, pelaksanaannya di sekolah dasar, khususnya di daerah dengan keterbatasan sumber daya, masih menghadapi berbagai kendala. Penelitian ini bertujuan untuk menganalisis problematika pembelajaran Pendidikan Agama Islam (PAI) di SDN 2 Gebang Sidoarjo yang tergolong sebagai sekolah dengan kategori 3T (terpencil, terluar, tertinggal). Fokus penelitian diarahkan pada identifikasi permasalahan pembelajaran PAI yang ditinjau dari aspek sumber daya manusia (SDM) guru, sarana dan prasarana pembelajaran, metode pembelajaran, serta minat dan partisipasi peserta didik. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode studi kasus. Pengumpulan data dilakukan melalui observasi partisipan, wawancara mendalam dengan kepala sekolah, guru PAI, dan peserta didik, serta analisis dokumen pembelajaran. Analisis data dilakukan dengan model interaktif Miles dan Huberman yang meliputi tahap reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa pembelajaran PAI di SDN 2 Gebang Sidoarjo menghadapi berbagai problematika yang saling berkaitan, antara lain keterbatasan jumlah dan kompetensi guru PAI yang harus merangkap sebagai guru kelas, minimnya sarana dan prasarana pendukung pembelajaran, dominasi metode pembelajaran konvensional akibat sistem kelas rangkap, serta rendahnya minat dan partisipasi siswa yang dipengaruhi oleh kurangnya variasi pembelajaran dan dukungan lingkungan keluarga. Simpulan penelitian ini menegaskan bahwa peningkatan kualitas pembelajaran PAI memerlukan upaya perbaikan yang komprehensif melalui penguatan kompetensi guru, penyediaan sarana prasarana yang memadai, penerapan metode pembelajaran yang kontekstual dan inovatif, serta penguatan kolaborasi antara sekolah, orang tua, dan masyarakat.